Frequent loss of heterozygosity on chromosome 6 in human ovarian carcinoma. - Foulkes, W; Ragoussis, I; Stamp, G; Allan, G; Trowsdale, J (1993)
Investigation of genetic changes in tumours by loss of heterozygosity (LOH) is a powerful technique for identifying chromosomal regions that may contain tumour suppressor genes. LOH has been described on chromosome 6 in ovarian carcinoma using restriction fragment length polymorphism analysis with a small number of probes. We studied 29 ovarian carcinomas with 19 probes mapping to chromosome 6. Sixteen of the 29 tumours showed LOH on 6q (55%). Of these 16, 63% showed loss of all informative markers on that arm. One tumour showed loss of 6q24-qter, localising the putative tumour suppressor gene to that region. Loss on 6p was 28% overall. However, using three dinucleotide repeat primer pairs from 6p to study LOH in seven selected tumours, LOH was demonstrated at both 6p22.3-pter and at 6p12-6p22. These results confirm that 6q harbours a tumour suppressor gene of relevance to ovarian carcinoma and suggest that there may also be a similar gene(s) on 6p. By Southern analysis, there was no evidence of genomic rearrangements of the oestrogen receptor gene, located at 6q25.1. LOH on 6q was more common in high than low grade tumours. The relevance of our findings to previous work in ovarian cancer and other solid tumours is discussed.